Awareness of age-related change in the context of major life events - Rupprecht, Fiona; Sabatini, Serena; Diehl, Manfred; Gerstorf, Denis; Kaspar, Roman; Schilling, Oliver; Wahl, Hans-Werner (Frontiers in psychiatry, 2022)
Although gains and losses are an integral part of human development, the experience of change and readjustment that often comes with major life events may be particularly influential for an individual's subjective aging experience and awareness of age-related change (AARC). Thus, this study focused on the role of life events in the domains of family and health for an individual's awareness of age-related gains and losses. Specifically, we differentiated between the experience of specific life events (e.g., entering a new romantic relationship; hospital stay) and the cumulative experience of multiple life events. Furthermore, we differentiated between life events experienced at an expected time in life and life events experienced relatively early or relatively late compared to established social norms. Data came from the Innovation Sample of the German Socio-Economic Panel (SOEP-IS) and consisted of 1,612 participants aged 16 to 93 years (M = 54.1; SD = 18.2). Life events were assessed annually and retrospectively for the last 2 years. Propensity score matching provided evidence for an association of specific family life events and a higher awareness of age-related gains, as well as specific health life events and a higher awareness of age-related losses. Results furthermore indicated that the cumulative experience of family life events was associated with a higher awareness of age-related gains. Conversely, the cumulative experience of health events was associated with higher awareness of both age-related losses and age-related gains. Moreover, it was not only life events happening at an expected age, but also those happening relatively early and particularly those happening late in life, which were associated with AARC. In summary, life events and the change they may bring seem to be reflected in individuals' awareness of age-related losses and awareness of age-related gains.